Polymorphic variants in DOCK7, ABCG8, UBE2E2, and SYN2 genes associated with type 2 diabetes in the Uzbek population - Zakirova, Darya; Abdullaev, Alisher; Dalimova, Dilbar; Aguryanova, Elina; Khonboev, Fazliddin; Khushvakova, Nilyufar; Alikhanova, Nodira; Takhirova, Feruza (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetes is a leading cause of death, affecting nearly half a billion adults worldwide. With projections indicating a significant increase in prevalence, understanding the genetic factors that contribute to diabetes, particularly type 2, is crucial.MethodsThis study investigated the association of specific polymorphisms with type 2 diabetes (T2D) in the Uzbek population. A total of 165 individuals, including 125 patients with T2D and 40 controls, were genotyped for variants located in the DOCK7, ABCG8, UBE2E2, SYN2, HNF1A, and IGF2BP2 genes using real-time polymerase chain reaction.ResultsThe analysis revealed significant associations between these polymorphisms and T2D under various genetic models. The distribution of the genotype frequencies was consistent with the Hardy–Weinberg equilibrium.ConclusionThe findings of this study underscore the importance of ethnic and geographical diversity in genetic studies and contribute to the understanding of T2D in the Uzbek population. Further research is needed to explore the clinical implications of these genetic associations.